KNOWLEDGE, ATTITUDE AND PRACTICE TOWARDS COVID-19 AMONG PATIENTS ATTENDING EAR, NOSE AND THROAT OUT-PATIENT DEPARTMENT AT A TERTIARY HOSPITAL - Rijal, Anupama Shah; Josh, Rupesh Raj; Shrestha, Kundan Kumar; Dhungana, Anup (Journal of Chitwan Medical College, 2022)
Background: The COVID-19 pandemic has ravaged the world and Nepal reported its first case on 23rd January 2020. Increasing people’s knowledge of the disease can modify attitude and change practice and is key in prevention. This study assessed the knowledge, attitude and practice (KAP) of patients presenting to the Ear, Nose and Throat (ENT) out-patient department (OPD). Methods: A hospital based cross-sectional study was conducted at the ENT OPD with 906 patients. Patients aged 20 years and above were studied regarding their KAP towards COVID-19. A questionnaire was used to collect data and analysed for gender, age group, education level and occupations. Statistical analysis was done using Mann-Whitney and Kruskal-Wallis tests. Results: Males had better knowledge and more positive attitude compared to females, which was statistically significant (p 0.001 and p 0.011). Similarly, there were significant statistical differences among the various age groups in knowledge (p <0.001), however, attitude and practice were not different. When KAP was compared to education, differences in knowledge and attitude were statistically significant p<0.001. Likewise, statistical differences existed with regard to knowledge and the various occupations (p <0.001), but a positive attitude was noted in all occupations. Practice was correct in the majority of studied groups with no statistical differences seen. Conclusions: Among the ENT patients correct practice was seen in all the groups namely, gender, age, education and occupation. However, there were differences in knowledge and attitude levels.